2018
DOI: 10.1016/j.jpainsymman.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Health Care Utilization at End of Life Among Older Adults With Advanced Non–Small-Cell Lung Cancer

Abstract: EOL healthcare utilization varied by timing of depression diagnosis. Those with pre-cancer depression had lower odds of high-intensity healthcare, were more likely to utilize hospice, and have longer hospice stays. Regular depression screening and treatment may help patients optimize decision-making for EOL care. Additionally, hospice providers may need additional resources to attend to mental health needs in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(67 citation statements)
references
References 68 publications
4
61
2
Order By: Relevance
“…We have also found that RMDD patients had a longer time between cancer diagnosis and death (median 426 vs. 327 days). This result is not consistent with previous studies suggesting that patients with severe mental illness may have a shorter time between diagnosis and death (Doan et al, 2016;Irwin et al, 2014;McDermott et al, 2018). This discrepancy may be due to specific factors of depression.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…We have also found that RMDD patients had a longer time between cancer diagnosis and death (median 426 vs. 327 days). This result is not consistent with previous studies suggesting that patients with severe mental illness may have a shorter time between diagnosis and death (Doan et al, 2016;Irwin et al, 2014;McDermott et al, 2018). This discrepancy may be due to specific factors of depression.…”
Section: Discussioncontrasting
confidence: 99%
“…After matching and adjustment, RMDD patients received more palliative care, less chemotherapy, dialysis, blood transfusion, surgery, imaging, more artificial nutrition and died less in the ICU/ED than controls. These RMDD characteristics are consistent with those of American studies (Doan et al, 2016;McDermott et al, 2018) who included patients with acute depression during the 12 to 24 months prior to cancer diagnosis, without excluding dementia, bipolar disorders and psychotic depression.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Geriatric oncology HSR spans the entire cancer care continuum, with patterns of care at the end of life representing another important area of investigation [60][61][62][63]. For example, using the SEER-Medicare dataset, end-of-life healthcare utilization has been shown to vary among older adults with a pre-cancer diagnosis of depression compared with a post-cancer diagnosis of depression [64]. However, robust linkages to EHR data are needed to determine if care at the end of life is aligned with patients' and families' goals and values.…”
Section: Patterns Of Care and Patient Outcomesmentioning
confidence: 99%